PRODUCT QUALITY ON CONSUMER PURCHASE INTEREST WITH CUSTOMER SATISFACTION AS A VARIABLE INTERVENING IN BLACK ONLINE STORE HIGH CLICK MARKET: Case Study on Customers of the Tebing Tinggi Black Market Online Store - Mangasi Sinurat; Mohd. Heikal; Amsal Simanjuntak; Rumiris Siahaan; Rico Nur Ilham (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2021)
Product Quality on Consumer Buying Interest with Customer Satisfaction as an Intervening Variable at the Tebing Tinggi Black Market Online Store (Case Study on Customers of Tebing Tinggi Black Market Online Store), Product Quality on Consumer Buying Interest with Customer Satisfaction as an Intervening Variable at the Tebing Tinggi Black Market Online Store. The research method used is the data method. qualitative and quantitative data. While the data used is primary data. The data analysis method in this study uses simple linear regression analysis to obtain a comprehensive picture of the effect of product quality variables on consumer buying interest using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of hypothesis testing using simple regression analysis and t-test show that: the t-table value of the Product Quality variable is 7.644> the t-table value (df: : 68%) of 1.995 so it can be concluded if Product Quality has a positive effect and significant to Consumer Buying Interest.